Comparative Analysis on Technology and Business System in Startups: A Case Study of PT CNC Part Teknika Indonesia and SuperCharge.SG Singapore - Purnamasari, Rita; Purwanto, Purwanto; Widjaja, Anton Wachidin; Haryanto, Jony Oktavian (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This research is a report based on the TUM project and based on direct observation in the company. The study compares the innovation strategies of two startups companies operating in the technology sector: Indonesian CNC parts manufacturer PT CNC Part Teknika and Singaporean solar powered electric vehicle charging solution provider SuperChargeSG. Using the McKinsey 7S framework, the study identifies the strengths, weaknesses, and best practices of both companies. The results show significant differences in strategies, structures, systems, and human resources. Singapore companies stand out with proactive and sustainable innovative approaches, while Indonesian companies tend to be more reactive. Based on these findings, the study provides recommendations for Indonesian companies to improve their competitiveness through market diversification, the development of organizational structures, the adoption of advanced technology, and the formation of a strong culture of sustainability innovation.